2019
DOI: 10.1167/iovs.19-27376
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Curcumin, a Plant Polyphenol Extracted From Curcuma longae, in Fibroblasts From Patients With Graves' Orbitopathy

Abstract: PURPOSE. We examined the therapeutic effect of nontoxic concentrations of curcumin, a plant polyphenol extracted from Curcuma longae, in primary cultures of orbital fibroblasts from Graves' orbitopathy (GO). METHODS. The effect of curcumin on interleukin (IL)-1b induced-proinflammatory cytokine production was determined using quantitative real-time PCR, enzyme-linked immunosorbent assay (ELISA), and Western blot analysis. Adipogenic differentiation was identified using Oil-Red O staining, and levels of peroxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…CUR also significantly reduced H 2 O 2 -induced ROS synthesis in fibroblasts. 188 The acute pharmacokinetics and pharmacodynamics of commercially marketed CUR capsules (4 g) in 12 normal, healthy volunteers with a standard breakfast were evaluated and plasma levels of CUR were detected by HPLC-ITMS/MS/MS. The major metabolite of CUR, curcumin-O-glucuronide, was detected at 30 min.…”
Section: Antioxidant Effects Of Curcumin Clinical Studiesmentioning
confidence: 99%
“…CUR also significantly reduced H 2 O 2 -induced ROS synthesis in fibroblasts. 188 The acute pharmacokinetics and pharmacodynamics of commercially marketed CUR capsules (4 g) in 12 normal, healthy volunteers with a standard breakfast were evaluated and plasma levels of CUR were detected by HPLC-ITMS/MS/MS. The major metabolite of CUR, curcumin-O-glucuronide, was detected at 30 min.…”
Section: Antioxidant Effects Of Curcumin Clinical Studiesmentioning
confidence: 99%
“…40,41 As such, evidence regarding the importance of Wnt signaling pathways in the patho-genesis of GO is mounting; recently, we found that suppression of the adipogenesis of GO fibroblasts by curcumin involved activation of the canonical Wnt signaling pathway, as well. 42 The changes in the phosphorylation of multiple transcription factors upon the addition of GSK-3β inhibitor in our GO fibroblasts indicate that a more complex network of signaling pathways may exist than once believed. Kumar et al 28 discovered that an auto-antibody against thyroid-stimulating hormone receptor stimulated the PI3K/Akt pathway downstream and induced adipogenesis of orbital preadipocytes in GO.…”
Section: Discussionmentioning
confidence: 82%
“… 40 , 41 As such, evidence regarding the importance of Wnt signaling pathways in the pathogenesis of GO is mounting; recently, we found that suppression of the adipogenesis of GO fibroblasts by curcumin involved activation of the canonical Wnt signaling pathway, as well. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have found that quercetin inhibits cigarette smoke extract-induced adipogenesis in GO fibroblasts by reducing ROS ( 48 ). Additionally, we have reported several molecules with anti-oxidative properties such as resveratrol, caffeine, and curcumin suppress adipogenesis in GO fibroblasts ( 49 51 ). Given that oxidative stress contributes to the proliferation of orbital fibroblasts ( 52 ), the impeded proliferation of GO fibroblasts by PCSK9 inhibition demonstrated in this study may be attributed to the anti-oxidative property of the PCSK9 inhibitor.…”
Section: Discussionmentioning
confidence: 99%